Readiness Factors for Hot Commissioning of Coal-Fired Power Plant - Isnaeni Ali, Fachri; Toriq Arif Ghuzdewan; Ashar Saputra (Rekayasa Sipil, 2026)
The successful execution of coal-fired power plant projects depends heavily on the effectiveness of the commissioning phase, particularly the hot commissioning stage, which marks the transition from construction completion to commercial operation. Inadequate readiness at this stage often leads to operational disturbances, repeated testing cycles, and delays in achieving commercial operation. Despite its critical role, commissioning readiness has received limited attention in existing readiness research, which predominantly focuses on pre-construction and early construction phases. This study aims to identify and prioritize readiness factors that significantly influence the successful execution of hot commissioning activities in coal-fired power plant projects. A survey-based quantitative research design was adopted, supported by qualitative thematic synthesis. Readiness factors were identified from the relevant literature and commissioning standards, classified into thematic categories, and evaluated using a structured questionnaire administered to experienced commissioning practitioners. The collected data were analyzed using mean score analysis and the Relative Importance Index (RII). The results indicate that all identified readiness factors are perceived as important, with eight factors classified as high priority (RII ? 0.90). The highest-ranked readiness factors include human resource capability and labor productivity readiness (RII = 0.9539), project team and organizational structure readiness (RII = 0.9415), and control, protection, and instrumentation system readiness (RII = 0.9385). These findings demonstrate that hot commissioning readiness is not determined solely by technical system completion but is strongly influenced by organizational capability, procedural discipline, and system reliability. This study contributes to readiness research by positioning commissioning readiness as a distinct and critical project phase. It provides quantitative, evidence-based guidance for prioritizing readiness efforts to support effective and timely hot commissioning.